Makna Kearifan Lokal “Petik Laut” dalam Pembentukan Karakter Sosial Siswa SDN Kalibuntu 2 - Jariyah, Ainun; Kaluge, Laurens; Roni Alim Ba’diya Kusufa (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study aims to explore the meaning of local wisdom "Sea Picking" as a learning resource in improving students' understanding of Social Sciences (IPS) at SDN Kalibuntu 2 Probolinggo Regency. Using qualitative methods and phenomenological approaches, this study explores the subjective experiences of students and teachers in the learning process involving the "Sea Picking" tradition. Data were collected through in-depth interviews, participant observations, and documentation, which allowed researchers to understand how involvement in these traditions affected student learning outcomes. The results of the study showed that the involvement of students in the "Sea Picking" activity not only increased their knowledge of the local culture, but also formed social character and positive values such as mutual cooperation and gratitude. Students reported increased interest and motivation in learning social studies, as well as better critical thinking skills after engaging in the activity. The implications of this study show that the integration of local wisdom in social studies learning can improve students' understanding and form better character. Therefore, it is important for VII educators to develop a more flexible curriculum and accommodate learning activities outside the classroom. This research also provides recommendations for teacher training in learning methods based on local wisdom, as well as the development of teaching materials that are more interactive and innovative.